AME'S REBRANDING STRATEGY TO BUILD BRAND IDENTITY AND ENHANCE STRONGER COMPETITIVENESS - Sentosa, Michelle Adelia; Christianna, Aniendya (International Review of Humanities Studies, 2025)
This research analyses AME's rebranding process to build a strong brand identity and increase competitiveness in the fashion industry. Using a descriptive qualitative method, data was collected through in-depth interviews, observations, and documentation studies. The results showed that AME's rebranding involved visual design changes as well as adjustments to the brand's vision and mission. The new illustration and packaging elements successfully attracted consumers' attention and created a positive experience, which resulted in increased sales and positive responses from consumers. The findings provide valuable insights into rebranding strategies in the fashion industry and their implications for brand identity and business performance, which are expected to serve as a reference for AME and other brands in designing effective rebranding strategies in a competitive market.